Zavisimost' variabel'nosti serdecnogo ritma ot kinetiki balansa tela u futbolistov - Mukhsin, I. K.; Gorbacheva, E. A.; Syshko, D. V. (Uchenye zapiski universiteta imeni P.F. Lesgafta, 2019)
The relationship between the processes of heart rate regulation and the kinetics of body balance at football players is determined. It is shown that the stability of the vestibular and motor analyzers determines the effectiveness of the body balance in case of a threat of loss of balance, while the biological cost of maintaining the body stability is determined. The decrease in energy consumption of the body balance is associated with a change in the contribution of the sympathetic and parasympathetic regulation channel to the heart rhythm. It was found that among the football players with less energy consumption, area and length of migration of the center of mass of the body with stable registration, the sympathetic contribution to the regulation of heart rhythm prevails.